Magnetism and electronic structure calculation of SmN. (4th March 2015) - Morari, C; Beiuşeanu, F; Di Marco, I; Peters, L; Burzo, E; Mican, S; Chioncel, L
Abstract: The results of the electronic structure calculations performed on SmN by using the LDA+U method with and without including the spin–orbit coupling are presented. Within the LDA+U approach, a N(2 p ) band polarization of about 0.3  μ B is induced by Sm(4 f )-N(2 p ) hybridization, and a half-metallic ground state is obtained. By including spin–orbit coupling the magnetic structure was shown to be antiferromagnetic of type II, with Sm spin and orbital moments nearly cancelling. This results into a semiconducting ground state, which is in agreement with experimental results.